2020
DOI: 10.1186/s12882-020-01953-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different urinary uric acid indicators in patients with chronic kidney disease

Abstract: Background: Mounting studies have shown that hyperuricemia is related to kidney diseases through multiple ways. However, the application of urinary uric acid indicators in patients with reduced renal function is not clear. In this study, we aim to determine the effects of renal function on various indicators reflecting uric acid levels in patients with chronic kidney disease (CKD). Methods: Anthropometric and biochemical examinations were performed in 625 patients with CKD recruited from Dept of Nephrology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Alterations in parameters such as blood urea, creatinine, uric acid, and serum electrolytes from normal ranges may reflect renal problems and nephron dysfunction [ 25 , 33 , 34 ]. Compared to the control animals, ACP at tested doses caused no significant change in creatinine, urea, and uric acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in parameters such as blood urea, creatinine, uric acid, and serum electrolytes from normal ranges may reflect renal problems and nephron dysfunction [ 25 , 33 , 34 ]. Compared to the control animals, ACP at tested doses caused no significant change in creatinine, urea, and uric acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 As an important indicator of kidney function, the estimated glomerular filtration rate (eGFR) should be paid close attention for early detection of renal function decline. 4,5 In normal physiology, eGFR usually decreases with age by 0.5-1.0 mL/min/1.73 m 2 per year. 6,7 Whereas rapid eGFR decline, a rapid progressive decline in GFR, is generally recognized as an early marker of progressive kidney disease, and has been identified to be associated with cardiovascular disease and all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…As an important indicator of kidney function, the estimated glomerular filtration rate (eGFR) should be paid close attention for early detection of renal function decline 4,5 . In normal physiology, eGFR usually decreases with age by 0.5–1.0 mL/min/1.73 m 2 per year 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…urate transporter 1 (URAT1), and organic anion transporter 4 (OAT4)), and with approximately 10% excreted 11 . As kidney function declines, uric acid is retained 12 . However, it has been demonstrated that renal impairment is accompanied by a significant compensatory increase in the fractional excretion of uric acid (FeUA) and in the excretion of uric acid per volume of glomerular filtration 12 .…”
Section: Introductionmentioning
confidence: 99%
“…As kidney function declines, uric acid is retained 12 . However, it has been demonstrated that renal impairment is accompanied by a significant compensatory increase in the fractional excretion of uric acid (FeUA) and in the excretion of uric acid per volume of glomerular filtration 12 . Furthermore, extra-renal uric acid excretion also increases as a compensatory response to reduced kidney excretion of uric acid 13 .…”
Section: Introductionmentioning
confidence: 99%